2018
DOI: 10.1186/s13584-018-0260-x
|View full text |Cite
|
Sign up to set email alerts
|

Do disabilities impede the use of information and communication technologies? Findings of a repeated cross-sectional study – 2003-2015

Abstract: BackgroundThe current research focuses on trends of Internet adoption and digital uses among people with disabilities over a thirteen-year period.MethodsThe study is based on data elicited from a repeated cross-sectional study collected by means of Annual Social Surveys conducted by Israel’s Central Bureau of Statistics between 2003 and 2015. The sample included 95,145 respondents, among them 22,290 respondents with disabilities.ResultsThe rate of Internet access and digital uses increased continuously among d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 71 publications
1
16
0
1
Order By: Relevance
“…Studies have repeatedly shown that persons with intellectual disabilities, similarly to other persons with a disability as well as members of society at large, can gain many benefits from the use of the Internet. In line with the human and social capital benefits suggested by Lissitsa and Madar [3], among the benefits of ICTs for persons with intellectual disabilities are greater social interactions, connectedness, participation in mutual support groups, and access to information [8, 9]. A recent review that focused on social media use by people with intellectual disabilities found that this online environment has a potential for positive social and emotional experiences for this population in the area of friendships, development of social identity and self-esteem, and enjoyment [10].…”
supporting
confidence: 73%
See 4 more Smart Citations
“…Studies have repeatedly shown that persons with intellectual disabilities, similarly to other persons with a disability as well as members of society at large, can gain many benefits from the use of the Internet. In line with the human and social capital benefits suggested by Lissitsa and Madar [3], among the benefits of ICTs for persons with intellectual disabilities are greater social interactions, connectedness, participation in mutual support groups, and access to information [8, 9]. A recent review that focused on social media use by people with intellectual disabilities found that this online environment has a potential for positive social and emotional experiences for this population in the area of friendships, development of social identity and self-esteem, and enjoyment [10].…”
supporting
confidence: 73%
“…To map some of the benefits of ICT use, the study conducted by Lissitsa and Madar [3] differentiated between using the Internet to gain human capital vs. social capital. Human capital relates to Internet use to seek information, including information related to health, products, and events [4].…”
mentioning
confidence: 99%
See 3 more Smart Citations